Temperature dependence of Charge Transfer Luminescence in Yb3+:YAG single crystal - Yaraslau Padrez; Vitalii Boiko; Juraj Kajan; Tomáš Gregor; Vira Tinkova; Renata Karpicz; Mykhailo Chaika (Optical Materials: X, 2024)
Charge Transfer Luminescence (CTL) processes play a major roles in Yb:YAG laser materials act as a source of energy losses decrease the performance of this material. In this work, the temperature dependence of CTL in Yb:YAG single crystal was investigated. A 375-nm picosecond laser source was used as the excitation source. It was shown that the change in temperature affects the emission intensity and the position maximum of CTL occurring between perturbated F+ centers and Yb3+ ions. The increase in the temperature caused the blueshift of CTL, while the emission intensity have the inverted U-shape. The measured luminescence lifetime of CLT was in the range of 8 ns – 13 ns and barely changes with temperature. The temperature dependence of the CTL parameters was explained by the change in the energy transfer processes between F+ centers and the charge transfer state of Yb:YAG single crystals.